Studi Komparatif atas Tafsir Laṭaifu al-Ishârât dan Tafsir Ruh al-Ma’ani tentang Lafaz Ithm - Dini Hasinatu Sa'adah; Hasan Bisri; Ahmad Hasan Ridwan (Jurnal Iman dan Spiritualitas, 2021)
Not infrequently, there is a gap between Sufi idealism and the reality between worship carried out in the Shari'a and Riyadah carried out. So it is not uncommon for lay views to show sinful acts. This is the background for researchers to focus on the interpretation of al-Qusyairi and al-Alusi on the word ithm in the Koran. This study aims to analyze the understanding of ithm in the perspective of two Sufi commentators more deeply. The approach used is the semantic theory according to Toshihiko Izutsu, the irfâni epistemology theory according to Abid al-Jabiri and the muqâran (comparative) method according to al-Farmawi. The results of this study are as follows: First, al-Qushairi interprets the word ithm in general, and focuses more on the context of the perpetrator. Meanwhile, al-Alûsi analyzes it in more detail with various contexts. Al-Alûsi interprets lafadz Ithm with the meaning of sin or a job that hinders the reward.